340 Improving maternal sleep via cognitive behavioral intervention: A randomised controlled trial from pregnancy to 2 years postpartum. (3rd May 2021) - Bei, Bei; Pinnington, Donna; Quin, Nina; Shen, Lin; Blumfield, Michelle; Wiley, Joshua; Drummond, Sean; Newman, Louise; Manber, Rachel
Abstract: Introduction: Maternal sleep disturbance is common during pregnancy and postpartum periods. This study evaluated the feasibility and efficacy of a scalable cognitive behavioural therapy (CBT) sleep intervention tailored for these periods. Methods: This is a two-arm, parallel-group, single-blind, superiority randomised controlled trial. Nulliparous women without major medical/psychiatric conditions were randomised 1:1 to CBT or active control of equal frequency/duration. All participants received a 1-hr telephone session and automated multimedia emails from the 3rd trimester until 6 months postpartum. Outcomes were assessed with validated instruments at gestation weeks 30 (baseline) and 35 (pregnancy endpoint), and postpartum months 1.5, 3, 6 (postpartum endpoint), 12, and 24. Results: 163 eligible participants (age M +/- SD = 33.35 +/- 3.42) were randomised. The CBT intervention was well accepted, with no reported adverse effect. Intention-to-treat analyses showed that compared to active control, receiving CBT was associated with lower insomnia severity and sleep disturbance (two primary outcomes), and lower sleep-related impairment at the pregnancy endpoint (p-values ≤ .001), as well as at 24 months postpartum (p ranges .012-.052). Group differences across the first postpartum year were nonsignificant. Women with elevated insomnia symptoms at baseline benefitted substantially more from CBT (vs control), including having significantly lower insomnia symptoms throughout the first postpartum year. Group differences in symptoms of depression or anxiety were nonsignificant. Conclusion: A scalable CBT sleep intervention is efficacious in buffering against sleep disturbance during pregnancy, with long-term benefits to maternal sleep, especially for women with sleep complaints during pregnancy. The intervention holds promise for implementation into routine perinatal care. Support (if any): Data collection was supported by Rob Pierce Grant-in-Aid and Helen Bearpark Scholarship from Australasian Sleep Association, Strategic Grant Scheme from Monash University, and the Royal Women's Hospital Foundation. Intervention materials were adapted from those developed via a National Institute of Health R01 grant (NR013662). Bei (APP1140299) and Wiley (APP1178487) are supported by National Health and Medical Research Council Fellowships, and Pinnington, Quin, Shen by Australian Postgraduate Awards by Department of Education and Training. The funder of the study had no role in study design, data collection, data analysis, data interpretation, or writing of the report.